Futebol, política e identidade nacional: uma análise das copas do mundo entre 1950 e 1958 - Souza, Flavio Antonio De [UNIFESP] (2019)
This study analyzes the relationship between soccer and politics in Brazilian society. After its popularization in the first decades of the twentieth century, soccer in Brazil was consolidated, in the view of the sports press, as one of the best in the world. The disputes of the World Cups of 1950, 1954 and 1958 are part of the context of the “Era Vargas”, characterized by, among other things, a strong tension between the nationalist project advocated by the ruling group and the liberal project, idealized by opposition groups that often used the mass media as instruments to carry out the political struggle. Therefore, the main objective of this work is to identify the action of communication vehicles linked to political parties in the construction of the idea of "soccer country", as well as in the tensions and political, social, cultural and racial conflicts that permeated Brazilian society at the time.